2011
DOI: 10.1097/inf.0b013e3181f728fd
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Immunity Following a Booster Dose of Haemophilus Influenzae Type B-Meningococcal Serogroup C Glycoconjugate Vaccine

Abstract: A toddler Hib-MenC-TT booster helps sustain immunity against Hib to 3½ years of age. Persistence of MenC antibody is similar in children primed with MenC-CRM197 in infancy who receive a booster Hib-MenC-TT, to those who receive no booster. Persistence of MenC antibody is better when primed and boosted with Hib-MenC-TT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…Decreases in SBA titers over time have also been demonstrated in other age groups, with more marked waning in children immunized at younger ages (3,13,17,19,20) and much better persistence demonstrated following immunization of older children and adolescents (19,21,22). A study evaluating MenC SBA titers in 11 to 20 year olds in the United Kingdom, approximately 5 years after immunization with a conjugate MenC vaccine, demonstrated that higher SBA titers were observed in children who had been vaccinated at age 10 years or older than in children who had been vaccinated at a younger age (21).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Decreases in SBA titers over time have also been demonstrated in other age groups, with more marked waning in children immunized at younger ages (3,13,17,19,20) and much better persistence demonstrated following immunization of older children and adolescents (19,21,22). A study evaluating MenC SBA titers in 11 to 20 year olds in the United Kingdom, approximately 5 years after immunization with a conjugate MenC vaccine, demonstrated that higher SBA titers were observed in children who had been vaccinated at age 10 years or older than in children who had been vaccinated at a younger age (21).…”
Section: Discussionmentioning
confidence: 90%
“…A catch-up campaign was launched over the subsequent 11 months that offered a single dose of vaccine to those aged between 1 and 18 years (later extended to 25 years of age). Previous studies have demonstrated rapid waning of MenCspecific antibody concentrations and serum bactericidal antibody (SBA) titers following immunization in young children (3,13,17,20) but much better persistence following immunization of older children and adolescents (19,21,22) Furthermore, the effectiveness of MenC vaccines is known to decline in populations whose SBA titers have waned over time (6). Thus, persistence of adequate levels of bactericidal antibody is important to ensure immunity for each individual.…”
mentioning
confidence: 99%
“…Accordingly, this is the most frequently used measure to assess the immunogenicity of Hib conjugate immunization schedules and to predict protection that will endure throughout the period of risk for infants, toddlers, and pre-school children. 10,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] Moreover, a study in the Dominican Republic has indicated that even higher serum PRP antibody levels, 5.0 μg/mL, can be correlated with protection against upper respiratory tract colonization with Hib. 17 Since 2002, the Center for Vaccine Development -Mali (CVD-Mali), in Bamako (a collaborative enterprise maintained jointly by the Ministry of Health of Mali and the Center for Vaccine Development of the University of Maryland School of Medicine), has been conducting systematic surveillance studies of invasive pediatric bacterial infections among infants and children admitted to l'Hô pital Gabriel Touré, the one government hospital where severely ill children are admitted.…”
Section: Introductionmentioning
confidence: 99%
“…A catch-up campaign was launched over the subsequent 11 months that offered a single dose of vaccine to those aged between 1 and 18 years (later extended to 25 years of age). Previous studies have demonstrated rapid waning of MenCspecific antibody concentrations and serum bactericidal antibody (SBA) titers following immunization in young children (3,13,17,20) but much better persistence following immunization of older children and adolescents (19,21,22) Furthermore, the effectiveness of MenC vaccines is known to decline in populations whose SBA titers have waned over time (6). Thus, persistence of adequate levels of bactericidal antibody is important to ensure immunity for each individual.…”
mentioning
confidence: 99%
“…Thus, persistence of adequate levels of bactericidal antibody is important to ensure immunity for each individual. In 2006, a combined Haemophilus influenzae type b (Hib)-MenC vaccine given as a booster dose at 12 months of age was introduced into the routine schedule in an attempt to sustain protection, but recent data show that antibody also wanes rapidly after this booster dose (3,13).…”
mentioning
confidence: 99%